Wet bulk micromachining characteristics of Si110 in NaOH-based solution. (1st December 2022) - Purohit, S; Swarnalatha, V; Pandey, A K; Sharma, R K; Pal, P
Abstract: Silicon wet bulk micromachining is an extensively used technique in microelectromechanical systems (MEMS) to fabricate variety of microstructures. It utilizes low-cost etchants and suitable for batch process that made it popular for industrial production. The etch rate and the undercutting at convex corner significantly affect the productivity. In wet anisotropic etching-based micromachining, Si110 wafer is employed to fabricate unique shape geometries such as the microstructures with vertical sidewalls. In this research, we have investigated the etching characteristics of Si110 in 10 M sodium hydroxide without and with addition of hydroxylamine (NH2 OH). The main objective of the present work is to improve the etch rate and the undercutting at convex corners. Average surface roughness ( R a ), etch depth, and undercutting length are measured using a 3D scanning laser microscope. Surface morphology of the etched Si110 surface is examined using a scanning electron microscope. The incorporation of NH2 OH significantly improves the etch rate and the corner undercutting, which are useful to enhance the productivity. Additionally, the effect of etchant age on the etch rate and other etching characteristics are investigated. The etch rate of silicon and the undercutting at convex corners decrease with etchant aging. The results presented in this paper are very useful to scientists and engineers who use silicon wet anisotropic etching to fabricate MEMS structures using bulk micromachining. Moreover, it has great potential to promote the application of wet etching in MEMS.